Heroin dependence duration influences the metabolic parameters: mechanisms and consequences of impaired insulin sensitivity in hepatitis C virus seronegative heroin dependents - Zanina Pereska; Cvetanka Bozinovska; Cedo Dimitrovski; Koco Cakalarovski; Andon Chibishev; Milka Zdravkovska; Aleksandra Babulovska; Daniela Janicevic (Hagerstown, MD : Lippincott Williams & Wilkins, 2012)
Carbohydrate metabolism disorder in heroin dependence is an issue with long history and contradicting results. The aim of the study was to evaluate basal insulin sensitivity in hepatitis C virus seronegative heroin dependents with normal body mass index, taking into consideration the duration of heroin dependence.
Keywords: dependence duration; heroin; HOMA-B%; HOMA-IR